(3fXe GdCQHYjf MOjKkGs - (3eLghds ((3SdjeGf GdJfh s)
(3ChdgG (B:s
(3hHYO aGYde CjgG GdeYGfi LhGeY Gdcde HGdeYGfi Efi eP SeYJ bhd Wg HGJ ef jMaX ef CdaGXg cYOI GdejbGJ ai MaGXg s
(3BNQgG (B:s
(3TQa HQbe gPg GdCHjGJ GdefXheI GdTQjaI HGdCMGOjK hGdCNHGQ GdefjaI CabQ GdhQi hCPd GdabQGA hCMhLge Edi GdMi GdOGFe GdPi dG jehJ YHO g SdjeGf GdJfh s
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs